(untitled) (Research, Society and Development, 2021)
Allelopathy can be used to combat weeds, which can negatively interfere in various natural and cultivated environments. Among the weeds found in the Caatinga are Calotropis procera and Cenchrus echinatus. Thus, the objective was to evaluate the allelopathic effect of extracts from leaves, stems and roots of Ziziphus joazeiro on the germination and development of these species. Two portions of 50 g of each part of the plant were used for 500 mL of distilled H20. The experiment consisted of six treatments: extract of leaves, stems and roots at 100 °C (infusion) and at 25 °C (cold), followed by a control group (distilled water). The analyzed parameters were: germination percentage, germination speed index and stem and radicle length. In general, germination percentage and IVG of C. echinatus were negatively affected by all tested treatments. Regarding the development of its seedlings, there was a significant interference in the development of the radicles. Regarding C. procera seeds, when compared to the control group, there was no statistical difference neither for germination percentage nor for IVG. Regarding the development, there was no interference neither for the stem nor for the radicle, with the exception of the hot infusion extract which inhibited the stem development. The results show that there was more efficient allelopathic interference on C. echinatus especially when subjected to the extract by infusion of the donor species bark.